2016
DOI: 10.1097/ijg.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Glaucoma Medications on Corneal Wound Healing

Abstract: Corneal toxicity of Xalatan is most probably caused by BAC. Monoprost delays corneal healing, which is not well understood. The Monoprost effects could be caused by its additive, macrogolglycerolhydroxystearate 40. This excipient is a known skin irritant, and its concentration is relatively elevated in Monoprost, 50 mg/mL, compared with its active ingredient, latanoprost (0.05 mg/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
(20 reference statements)
1
22
1
3
Order By: Relevance
“…Pinheiro et al found that 0.02% BAK aggravated corneal abrasions from 14.65 mm 2 to 66.57 mm 2 to87.26 mm 2 in area. Iatrogenic corneal abrasions were healed completely and recovered corneal stroma (Descemet’s membrane) structure in the Tafuprost use group, but delayed corneal healing markedly in the Latanoprost use group [5]. Fogagnolo et al studied the confocal microscopic findings of non-preservative tafluprost and latanoprost in glaucoma patients for 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pinheiro et al found that 0.02% BAK aggravated corneal abrasions from 14.65 mm 2 to 66.57 mm 2 to87.26 mm 2 in area. Iatrogenic corneal abrasions were healed completely and recovered corneal stroma (Descemet’s membrane) structure in the Tafuprost use group, but delayed corneal healing markedly in the Latanoprost use group [5]. Fogagnolo et al studied the confocal microscopic findings of non-preservative tafluprost and latanoprost in glaucoma patients for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Benzalkonium chloride (BAK) is the most used preservative and is excellent for safety and stability of drug. However, it causes dry eye, corneal oedema, corneal erosion, and corneal toxicities, thus lowering the long-term tolerability for patients [57]. A critical component when managing glaucoma patients is ensuring compliance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although latanoprost is generally well-tolerated, previous studies in a variety of systems revealed that latanoprost formulations that contain the preservative BAK can have detrimental effects on corneal cells. Among these effects are epithelial cytotoxicity 73 – 75 , an increase in the incidence of ocular surface disease 76 78 , and delays in corneal wound healing 79 . All of these effects are largely dependent on BAK 75 , 80 , 73 – 81 .…”
Section: Discussionmentioning
confidence: 99%
“…При сравнительной оценке частоты побочных эффектов у различных представителей ана-логов простагландинов было отмечено, что применение Латанопроста, травопроста и биматопроста приводит к одинаковым побочным эффектам. Известно, что ча-стота и выраженность нежелательных явлений при при-менении офтальмологических препаратов может зави-сеть не только от действующих, но и от вспомогатель-ных веществ в их составе, включая консервант [2,3]. С этой точки зрения наибольший интерес представляет изучение глазных капель, не содержащих консерванты [4,5], в том числе, препаратов в тюбик-капельницах од-норазового применения по сравнению с препаратами с консервантом в традиционных флаконах [5].…”
Section: Ophthalmology In Russia 2016;13(3):191-196unclassified